Development and functional evaluation of a psoralen-conjugated nucleoside mimic for triplex-forming oligonucleotides - Yu Mikame; Haruki Toyama; Chikara Dohno; Takehiko Wada; Asako Yamayoshi (Communications Chemistry)
Abstract Psoralen-conjugated triplex-forming oligonucleotides (Ps-TFOs) have been employed for the photodynamic regulation of gene expression by the photo-cross-linking of psoralen with the target DNA. However, stable triplex formation requires a consecutive purine base sequence in one strand of the target DNA duplexes. The pyrimidine-base interruption in the consecutive purine base sequence drastically decreases the thermodynamic stability of the corresponding triplex, which hampers the TFO application. Here, we propose a design of the Ps-TFO for stable triplex formation with target DNA sequences containing pyrimidine-base interruptions under physiological conditions. This Ps-TFO, named 1’(one)-psoralen-conjugated triplex-forming oligonucleotide (OPTO), incorporates a synthesized nucleoside mimic 1’-psoralen-conjugated deoxyribose to increase the thermodynamic stability of the corresponding triplex by the intercalation of psoralen. The triplex-forming abilities of the OPTO were successfully demonstrated in combination with LNA and 5-methylcytosine, indicating that the use of OPTO will expand the range of the target sequences of TFO for photodynamic gene regulation.